MXene/carboxymethylcellulose-polyaniline (Ti3C2Tx/CMC-PANI) film as flexible electrode for high-performance asymmetric supercapacitors. (20th December 2022) - Xu, Hanping; Cui, Linlin; Lei, Zijie; Xu, Mincai; Jin, Xiaojuan
Abstract: Two-dimensional (2D) MXene (Ti3 C2 Tx ) materials have received widespread attention as potential electrodes for supercapacitors due to their solution processability, metallic conductivity and excellent energy storage properties. Unfortunately, the self-stacking and interlayer interactions of Ti3 C2 Tx flakes cause them to acquire poor electrochemical characteristics. Herein, the interwoven carboxymethylcellulose-polyaniline (CMC-PANI) composites were prepared by in-situ polymerization of aniline on the surface of CMC, which was subsequently used as the intercalators to expand the layer spacing of Ti3 C2 Tx nanosheets via a facile self-assembly process. The interwoven CMC-PANI bridges horizontal Ti3 C2 Tx nanosheets to construct interconnected conductive and ion channels, making the internal structure of the Ti3 C2 Tx /CMC-PANI (TCP) film more uniformly and orderly, thereby achieving a high mechanical strength (≈ 35.6 MPa). Meanwhile, the TCP film exhibits a maximum area specific capacitance of 1161.4 mF cm −2 (812.9 mC cm −2 ) at 1 mA cm −2, and a superior rate performance (maintains 58.4% of the initial value at 50 mA cm −2 ). Moreover, the fabricated asymmetric supercapacitor (ASC) device presents a high area energy density of 158.7 µW h cm −2 at a power density of 700.1 µW cm −2 and good cycle stability (retention of 89.6% after 15, 000 charging/discharging cycles). This rational design balancing flexibility and electrochemical performance provides a broadened idea to solve the inherent defects of MXene and further develop high performance energy storage devices.